Treatment of the chronic hepatitis C complicated by mixed cryoglobulinemia with direct-acting antiviral agents - N. V. Dunaeva; E. Yu. Kolpashchikova; S. Yu. Romanova; S. N. Kizhlo; S. V. Lapin; D. A. Gusev (Журнал инфектологии)
The aim of the study was to evaluate clinical, immunologic and anti-viral efficacy of antiviral therapy (АVT) with drugs of the direct antiviral action (DAA) of the chronic hepatitis C (CHC) complicated with secondary mixed cryoglobulinemia in small cohort of patients. Patients and methods: The cohort consisted of 12 patients with CHC (without signs of a coinfection of HIV, a hepatitis B virus) complicated with mixed cryoglobulinemia (criocrit more than 5% and presence of cryoglobulinemia-related symptoms). Standard DAA based therapy was indicated in all patients: 2 cases daclatasvir and asunaprevir, 3 cases daclatasvir and sofosbuvir and 7 cases Dasabuvir;Ombitasvir+Paritaprevir+Ritonavir. Results: Anti-viral response at 12 and 24 weeks was found in 91,6% (11/12) treated patients. In one case (on the daclatasvir and asunaprevir) resistance to both drugs developed. Clinical response was confirmed in 83% – 10/12 (25% – the complete response, 58% – the partial response). Despite of anti-viral response kidney damage persisted in 2 patients without apparent improvement. There was one lethal outcome at 25th week since the beginning of treatment because of bilateral pneumonia and thromboembolism in patient with kidney involvement treated with steroids and cytostatics. In 25% of patients total elimination of cryoglobulins was confirmed by the end of AVT and in 75% dramatic decrease of criocrit was found. Conclusion: We confirmed good virologic, clinical and immunologic response and safety of AVT with DDA in patients with HCV induced crioglobulinemia, especially when using schemes with a high genetic barrier (daclatasvir and sofosbuvir, Dasabuvir;Ombitasvir+Paritaprevir+Ritonavir).